Pembahasan Perhitungan Matematis Dan Simulasi Project Buck-Boost Converter Dengan Penerapan Pada PLTA Sederhana - Putri Kusuma Dewi; Andisa Julia Almira; Adenalia Syaharani; Najwa Armedia Rahmadianti; Denny Oktavina Radianto (KOLONI, 2024)
The increasing need for electricity for the community and the cost constraints for using fossil energy, require innovation in creating electricity sources using hydropower (PLTA). To increase the efficiency and stability of the output wave, a converter is installed in this circuit which can produce an output voltage that is lower or higher than the input voltage by using a PWM switch duty cycle. By installing a converter in a hydropower generating circuit, of course it cannot accommodate very large amounts of voltage due to the limited specifications of the components used. The Buck-Boost circuit used must use accurate mathematical calculations and must be simulated first to prevent and minimize the occurrence of errors and undesirable things.